The potential rise of an Islamist youth within 25 January revolts: a case study of the Muslim Brotherhood youth - Hosni, Dina (AUC Knowledge Fountain, 2013)
The thesis endeavors to offer a fresh perspective on the potential rise of Islamist youth, focusing on the pro-change ex-current MB youth as a potential subculture within 25 January and the assumption of the Egyptian MB to power. To validate this hypothesis, Gramsci's theory on hegemony and counter-hegemony has been deployed to study the rise of pro-change MB youth against Mubarak's authoritarian regime on the state level in tandem with counter-hegemony against the strict al-samc w-al-ṭāca principle (i.e. blind obedience) on the organizational level. Elements of social movement theory have been used to substantiate the relevance of counter-hegemony, namely, Gamson's three components of collective action frames; injustice, agency and identity. Mannheim's generational model has also been employed in the study as a unit of analysis to distinguish between pro-change ex-current MB youth representing the focus of the study and supportive MB youth. With concern to analytical orientation, the study has deployed mostly qualitative research methods based on primary sources in the form of 30 semi-structured interviews, in addition to content analysis of scholarly articles and books, web logs, in addition to journalistic material, drawing on the concepts of counter-hegemony and collective action frames. The analysis has demonstrated that the 2005 MB parliamentary victory which has heralded the success of the MB hegemonizing project, has generated the first traces of the rise of a youth subculture which has grown to pinnacle with the 25 January Revolution and its after effects. Based on the analysis, the cohort of MB youth could be categorized into two groups: those supportive of the MB, and those critical of the MB performance. The latter group which is the focus of the present study could be further branched into two orientations: those who still believe in reform from within keeping a vigilant eye on the Organization's performance, and those who could no longer tolerate MB's performance and thus have drifted away from the organization in order to establish or join other parties or groups, or have possibly remained independent. Content analysis has also shown that the pro-change ex-current MB youth have developed their own worldview as differing from that of the parent culture where they have opted accordingly for their own sphere of activity regardless of the Organization while staying committed to the general ideas of al-Banna. In line with Gamson’s three collective action frames, those youth have experienced feelings of ‘injustice’ directed toward the MB Organization which has excluded them from the decision-making process. Within the ‘agency’ frame, a number of those youth have sought the Cyber sphere as a type of liberating educational experience. Through their interaction with other youths whether in the cyber or public sphere, they have found common grounds with other Egyptian youths as could be translated in Revolution Youth Coalition (I’tilaf Shabāb al-Thawra), al-Tayyar al-Misriy (The Egyptian Current) Party under construction and Misr al-Qawiyya (Strong Egypt) established by splintering MB youth groups. The ‘identity’ frame within Gamson’s classification has emerged within the 25 January revolution and within its after effects as a form of resistance to the MB's excessive restrictions on the organizational level conspicuously in the dismissal of Aboul Fotouh and the establishment of the FJP to be the only MB party. The analysis has further shown that though no war of movement has materialized within those youth counter-hegemonic activities against the MB, they could still pose some challenges for the Organization, which merit further research in the topic.